2007
DOI: 10.2320/matertrans.mj200747
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relaxation and Crystallization of a Zr<SUB>44</SUB>Ti<SUB>11</SUB>Cu<SUB>9.8</SUB>Ni<SUB>10.2</SUB>Be<SUB>25</SUB> Bulk Metallic Glass

Abstract: The influence of annealing on the structural changes and the room temperature mechanical properties of a Zr 44 Ti 11 Cu 9:8 Ni 10:2 Be 25 bulk metallic glass has been investigated. The structural evolution upon relaxation or crystallization after annealing at a temperature within the supercooled liquid region was studied by thermal analysis, x-ray diffraction, transmission electron microscopy, extended x-ray absorption fine structure and dilatometer measurements. The effects of structural relaxation and nanocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…However, it should be noted that structural relaxation is strongly time-dependent and usually occurs in bulk of the sample causing large dilatation in amorphous alloys/BMG (∼3%, Fig. 4 [16,21]). In the present work, there is no holding time involved during sintering.…”
Section: Influence Of Processing Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it should be noted that structural relaxation is strongly time-dependent and usually occurs in bulk of the sample causing large dilatation in amorphous alloys/BMG (∼3%, Fig. 4 [16,21]). In the present work, there is no holding time involved during sintering.…”
Section: Influence Of Processing Parametersmentioning
confidence: 98%
“…This implies a decrease in the distance between nearest-neighbor atoms. Such a decrease in the atomic distance in the amorphous phase can lead to structural dilatation and eventually to nanocrystallization (usually observed in amorphous alloys [16][17][18][19][20][21]). In Fig.…”
Section: Structural Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The hardness of BMGs is reported to continuously increase upon structural relaxation, possibly because the excess free volume in the glass is annealed out, which is known to enhance the atomic bonding strength after annealing [19,20]. Furthermore, it is well known that structural relaxation-induced embrittlement has a detrimental effect on plastic deformation.…”
Section: Resultsmentioning
confidence: 97%
“…Studies of the thermal stability of amorphous alloys are of great importance. Although many research studies explore structures and properties of amorphous alloys during annealing [4][5][6], few studies are reported regarding the influence of circle heating on the stability of bulk amorphous alloys. This paper uses laser pulses as a heat source to investigate crystallization and thermal fatigue properties of the typical Zr 41 Ti 14 Cu1 2.5 Ni 10 -Be 22.5 bulk amorphous alloy.…”
Section: Introductionmentioning
confidence: 99%